Consumption patterns and eating behaviors of schoolchildren associated with mental health problems: a Brazilian nationwide study - Marília Barreto Pessoa Lima Rodrigues; Giovanna Angela Leonel Oliveira; Ariene Silva do Carmo; Jéssica Pedroso da Silva; Eduardo Yoshio Nakano; Vivian S. S. Gonçalves; Natacha Toral (PLoS ONE, 2025)
Background Children’s health should be analyzed in a broad context that considers different determinants. Few population-based studies have been conducted, especially with children about food consumption and eating behaviors associated with mental health. This study aimed to assess the association of consumption patterns and eating behaviors with mental health problems in Brazilian schoolchildren. Method The participants were children between 6 and 11 years old (n = 1967) from Brazilian schools and their parents. The child’s food intake was assessed using the Questionnaire on Food Consumption for Brazilian Schoolchildren (QUACEB), and the Illustrated Questionnaire on Eating and Sedentary Behaviors (QUICAS) was used to assess eating behavior. The child’s mental health was investigated using the Portuguese version of the Strengths and Difficulties Questionnaire. Principal component analysis was performed to identify consumption patterns and eating behaviors. Results Children with higher consumption of ultra-processed foods, less healthy food diversity, and unhealthy eating behaviors (eating distractedly with screens, alone, at irregular times, snacks, or processed foods, and not participating in kitchen tasks before or after meals) had a 45% higher chance of having mental health problems (OR 1.45; CI 1.12–1.87). Conclusions There is an association between consumption patterns and eating behaviors with mental problems in Brazilian schoolchildren. Our results reinforce the importance of analyzing the set of health determinants.